2004
DOI: 10.1055/s-2004-832842
|View full text |Cite
|
Sign up to set email alerts
|

Erbium(III) Triflate: A Valuable Catalyst for the Rearrangement of Epoxides to Aldehydes and Ketones

Abstract: Rearrangement of epoxides is performed with erbium triflate as catalyst. In contrast to most proposed catalysts for this reaction, erbium triflate works well with both aromatic and aliphatic epoxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…The catalyst amount is critical for every epoxide: aromatic epoxides, such as styrene oxide (1a), needed only 0.1% mol ( Table 1, entry 1) since, with higher catalyst percents, considerable amounts of phenylacetaldehyde (the rearranged product) are recovered. [22] In the case of aliphatic epoxides, where the rearrangement process is slower, [22] the reac-tion is better performed with 1 mol % of catalyst. Higher amounts of catalyst did not influence the reaction rate significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst amount is critical for every epoxide: aromatic epoxides, such as styrene oxide (1a), needed only 0.1% mol ( Table 1, entry 1) since, with higher catalyst percents, considerable amounts of phenylacetaldehyde (the rearranged product) are recovered. [22] In the case of aliphatic epoxides, where the rearrangement process is slower, [22] the reac-tion is better performed with 1 mol % of catalyst. Higher amounts of catalyst did not influence the reaction rate significantly.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, erbium triflate has proved to be a highly efficient and regioselective catalyst for the rearrangement of epoxides to carbonyl compounds. [22] The capability of erbium to coordinate the oxygen atom of the three-membered epoxy ring prompted us to explore other reactions involving epoxides, which can be catalyzed by erbium(III) triflate. In this communication we present the direct conversion of epoxides to acetonides catalyzed by this mild and environmentallyfriendly Lewis acid catalyst, in order to obtain a one-step stereoselective procedure to convert epoxides into protected diols.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that erbium triflate is a very efficient catalyst for the regioselective rearrangement of epoxides to carbonyl compounds, performing well on a wide range of substrates. [19] Although many assays were undertaken, only the most significant ones are compiled in Table 1. Thus, the treatment of styrene oxide (5a) with 0.5 mol % of erbium triflate in dichloromethane at 23 ºC for 20 min led to the formation of phenylacetaldehyde (2a) in 40% yield, remaining in the reaction mixture a 35% of the starting epoxide 5a, meanwhile, partial decomposition of aldehyde 2a through probably aldol condensation (around 25%) was also observed (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…, 226 (14), 225 (100), 183 (24), 175 (26), 135 (20), 132 (48), 120 (43), 114 (19), 107 (67), 57 (41), 43 (15) Supporting Information (see footnote on the first page of this article): Procedures and characterization data for epoxides 5c, 5d, 5f and 5g, and copies of 1 H, 13 C NMR and DEPT spectra for all the reported compounds.…”
mentioning
confidence: 99%
“…In fact its pK H and WERC values are 7.9 and 1.4 x 10 8 respectively, which are perfectly in accordance to Kobayashi statement. 12 Nevertheless, Er(III) triflate has so far been neglected among lanthanide triflates, as useful and environmentally friendly catalysts for many acid-catalyzed reactions, such as the acylation of alcohols, 13 or dioxolane protection removal, 14 epoxide rearrangement, 15 and the synthesis of Cpseudoglycals. 16 In this paper we demonstrate that erbium triflate is a very valuable catalyst for the synthesis of both acylals of aldehydes and enol esters of ketones.…”
mentioning
confidence: 99%